2022
DOI: 10.1039/d1gc04347a
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic complexation of phenol functionalized polymer induced in situ microfiber formation for 3D printing of marine-based hydrogels

Abstract: The design of 3D printable bio-based hydrogels with enhanced mechanical properties and minimal chemical modification can open new opportunities in the field of biomedical applications. A facile and safe approach...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 71 publications
(111 reference statements)
0
12
0
Order By: Relevance
“…We previously showed that enzymatically crosslinked phenolated chitosan-alginate revealed a similar FTIR spectrum compared to the individual chitosan and alginate hydrogel with a shift in the carboxylate groups of alginate. Besides, the amide I band of chitosan disappeared and overlapped with the carboxylate groups of alginate, indicating the formation of electrostatic interaction between the positively charged chitosan and negatively charged alginate (Jafari et al, 2022). The broad peak at 3260 cm -1 is attributed to the OH and NH stretch, and the sharp peak at 1570 corresponds to the amide I of chitosan and carboxylate stretch of alginate, which overlapped due to the electrostatic interaction (Ho, Mi, Sung, & Kuo, 2009).…”
Section: Hydrogel Fabricationmentioning
confidence: 98%
See 1 more Smart Citation
“…We previously showed that enzymatically crosslinked phenolated chitosan-alginate revealed a similar FTIR spectrum compared to the individual chitosan and alginate hydrogel with a shift in the carboxylate groups of alginate. Besides, the amide I band of chitosan disappeared and overlapped with the carboxylate groups of alginate, indicating the formation of electrostatic interaction between the positively charged chitosan and negatively charged alginate (Jafari et al, 2022). The broad peak at 3260 cm -1 is attributed to the OH and NH stretch, and the sharp peak at 1570 corresponds to the amide I of chitosan and carboxylate stretch of alginate, which overlapped due to the electrostatic interaction (Ho, Mi, Sung, & Kuo, 2009).…”
Section: Hydrogel Fabricationmentioning
confidence: 98%
“…Chitosan and alginate were conjugated by phenol groups through reaction with 3-(4-hydroxyphenyl) propionic acid and tyramine, respectively, using carbodiimide coupling chemistry according to our previous study (Jafari et al, 2022). The conjugation of chitosan-3-(4-hydroxyphenyl) propionic acid (Ch-Ph) and alginate-tyramine (Alg-Ty) was monitored by 1 H NMR and Ultraviolet-visible spectroscopy.…”
Section: Chitosan and Alginate Modificationmentioning
confidence: 99%
“…Notably, the biomineralized nanosheet contained catalase entrapped during its synthesis which works in concert with glucose oxidase by removing its reaction product H 2 O 2 in a cascade reaction and raises the overall glucose removal rate of the hydrogel. Recently, Shavandi and co-worker [ 77 ] functionalized both chitosan and alginate with phenol side groups and printed the double-crosslinked chitosan alginate hydrogel (DCCA) for biomedical applications. The first crosslinking mechanism was through the electrostatic attractions between the positively charged chitosan with negatively charged alginate forming a polyelectrolyte complex while the second mechanism was by covalent bonding through an enzyme-mediated formation and recoupling of α-carbon and or phenoxy radicals using horseradish peroxidase and H 2 O 2 .…”
Section: Immobilization By Physical Entrapment During 3d Printingmentioning
confidence: 99%
“…The cytocompatibility of hydrogels was evaluated through live/dead assay using 3T3 L fibroblast cell line and 3-(4,5-dimethylthiazol-2-yl)-5(3-carboxymethonyphenol)-2-(4-sulfophenyl)-2H-tetrazolium (MTS), [45]. First, the 3T3 L fibroblast cells were seeded on the hydrogel at a cell density of 10 4 cells/well in a 96-well plate for 3 days at 37 C and the cell culture media was renewed every day.…”
Section: D Cell Encapsulation and Hydrogel Cytocompatibility Testsmentioning
confidence: 99%
“…In the present study enzymatic crosslinking has been proposed since it employs mild physiological conditions suitable for making hydrogels from natural polymers, thus avoiding the risk of losing their bioactivity in a strong chemical environment [29]. Enzymatic crosslinking is also preferred when the hydrogel is to be employed in enclosing biomolecules and living cells while also promoting high site-specificity and diminishing the potential for the formation of harmful by-products [30][31][32]. In addition to horseradish peroxidase (HRP), other enzymes such as transglutaminase and tyrosinase have also been employed in the production of hydrogelation.…”
Section: Introductionmentioning
confidence: 99%